Multicam Studio Design Using Vmix As A Learning Media In SMK Bina Am Ma'mur: Leon Yudi Haryanto - leon yudi haryanto leon; Abdul Hayat; Abdul Hamid Arribathi (ADI Publisher, 2021)
The media is a tool that intersects in the process of teaching and learning for the achievement of educational goals in general and learning objectives in schools in particular. The media is also a means of transporting messages or information that is instructional or contain teaching purposes and is therefore called learning media. Many benefits can be taken from media management from what we know so far. The practical benefits of instructional media in the teaching and learning process are learning media that can clarify the presentation of messages and information so as to facilitate and improve the process and learning outcomes. The use of instructional media with multicam studio design using vmix can increase student motivation and can also affect student achievement or learning outcomes. It is expected that the results of this learning media will have an impact on increasing students in learning the basics of multimedia systems, as well as a question and answer activity to increase student activity in the learning process.